Researcher Profile: An Interview with Dr. Jeff Dew - Jeffrey Dew (Journal of Financial Therapy, 2012)
Jeff Dew earned a dual-title Ph.D. in Human Development and Family Studies and Demography from Pennsylvania State University. He then completed a two-year research post-doctoral position in Sociology at the University of Virginia. He has been an assistant professor in the department of Family, Consumer, and Human Development at Utah State University for three years. Dr. Dew sees himself as a family studies researcher who is interested in how financial issues are associated with relationship quality.
Keywords: family studies; financial therapy